2021
DOI: 10.1007/s42058-021-00075-1
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT performance and features of COVID-19 in the region of Abu Dhabi, UAE: a single institute study

Abstract: Objective We aim to investigate high-resolution CT features of COVID-19 infection in Abu Dhabi, UAE, and to compare the diagnostic performance of CT scan with RT-PCR test. Methods Data of consecutive patients who were suspected to have COVID-19 infection and presented to our hospital were collected from March 2, 2020, until April 12, 2020. All patients underwent RT-PCR test; out of which 53.8% had chest CT scan done. Using RT-PCR as a standard reference, the sensitivity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…There was significant correlation between clinical severity and death, fibrosis at 3 and 6 months. GhufranArefSaeed et al [37] in their study concluded that the oxygen requirements and length of hospital stay were increasing with the increase in scan severity. MehrdadNabahati et al…”
Section: Discussionmentioning
confidence: 97%
“…There was significant correlation between clinical severity and death, fibrosis at 3 and 6 months. GhufranArefSaeed et al [37] in their study concluded that the oxygen requirements and length of hospital stay were increasing with the increase in scan severity. MehrdadNabahati et al…”
Section: Discussionmentioning
confidence: 97%
“…The purpose of this study was to describe the chest HRCT scan findings in patients with COVID-19 and to compare the accuracy of HRCT with that of the current gold standard, PCR. 10,11,12,13,14,15,2,11,3,3,16,17 Chest HRCT findings…”
Section: Discussionmentioning
confidence: 99%
“…2. Single center research is more common 31 . For a large scale of the world, the model based on a single central sample training lacks universality, so it is difficult to achieve the degree of promotion.…”
Section: Discussmentioning
confidence: 99%